Extension through women and groups: an innovative approach of KVK gadag, Karnataka - M.J.Chandre Gowda,; S.H. Adapur,; R. Sudha, (Journal of Agricultural Extension Management, 2025)
Agricultural extension in India, largely done by the public sector, is primarily aimed at short-term changes like adoption of the innovations with less emphasis on farmers' capacity building, particularly on decision making in important aspects like farm management, combination and proportion of different enterprises towards diversification, timely switch-over from nonprofitable activities and the marketing aspects. Financial management of farm activities was also given less importance as compared to the production technologies. These efforts did not yield the desired results because the actual users of these intended technologies, who were women in most cases, were not directly involved. Thus, the current status of agricultural extension services could be summed up as largely in the public sector, operated in an interpersonal mode of select contact farmers and with low level of involvement of farmers in technology development and dissemination process. As it is substantially top-down, there is little scope for localised planning and action. Hence, several system constraints (ICAR, 1999) which have been listed below, have reduced the extension efficiency